ESTUDOS SÔBRE A MORTALIDADE POR SUICÍDIO. IV - A mortalidade por suicídio no Município do Recife - Ramos, Reinaldo; Barbosa, Victório (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1966)
This paper, one more in a series on suicide, analyses suicide mortality related to the period covering 1952 to 1963 in the City of Recife (Brazil). Details are given for this last year. Suicide relationships with sex, race and age are also analysed.